Kajian Tindak Tutur Ilokusi dalam Serial Drama Turki “Sultan Abdul Hamid II Episode 1”: The Study of Illocutionary Acts in Turkish Drama Series “Sultan Abdul Hamid II Episode 1” - Nahdliyyatul Azimah; Rahman Hakim; Khoirin Nikmah (Universitas Ahmad Dahlan, 2022)
The prestige of Turkish drama series in the world cinema is considered worthy of appreciation. Every drama that is presented can grab the attention of the audience. It is because of some elements such as theme, genre, storyline, and setting. One of the Turkish dramas that have caught the public attention is the drama series of Sultan Abdul Hamid II. This study aims to describe illocutionary speech as well as the meaning of the utterances contained in this drama series. This is qualitative descriptive research. The data collection technique used was the speaking-free listening technique. Meanwhile, the data analysis techniques used were (1) recording the utterances contained in the series Sultan Abdul Hamid II episode 1, (2) collecting and classifying utterances, and (3) describing the intent of the utterances. Based on the results of data analysis, there are four types of illocutionary, including directive, declarative, representative, and expressive. In directive utterances, utterances are related to the actions of ordering, begging, requesting, forbidding, and suggesting. Then, in the utterance of the declaration, there are elements of affirmation that contain the intention of glorifying, deciding, maintaining secrecy, and satirizing. Meanwhile, representative utterances are related to utterances that intend to state, to reveal, to report, and to describe. Then in expressive speech, various expressions express the intention of praising, praying, expressing thanks, admiration, satirizing, and conveying joy.